Distribution of selected trace elements and stable isotopes at various trophic levels of Sungai Pulai Estuary, Johor, Malaysia - Mukhtar, Aqilah (2015)
Trace metals in food web of seagrass ecosystem of Sungai Pulai in South of Johor was determined using combination of stable isotopes and heavy metals analyses. Stable isotope analysis was applied in order to construct the food web of seagrass area referred to the scientific ratios of δ13C and δ15N. In general, complex structure of seagrass ecosystem consisted of five trophic levels. Primary producers were located in the first trophic level, while second and third trophic levels consist of echinoderms and mollusks. Fish and mollusk made up in trophic level four and five. Selected trace metals (Co, Ni, As, Cd and Pb) concentration were evaluated in sediments and marine organisms to determine the metal pollution status effected from the anthropogenic activities around the ecosystem. In this study, total heavy metal and sequential extraction technique were used to determine the concentrations of metals in sediments. Result showed concentration pattern of trace metals for total extraction technique of sediment can be arranged as Ni > Pb > As > Co > Cd. While, arrangement of trace metals for sequential extraction technique such follows: Pb > Ni > As > Co > Cd. Distribution of trace metals in sediment come from both naturally occurrence and anthropogenic activities. However, most of metal sources present are naturally on the earth’s crust. After having assessment of Enrichment Factor (EF), Geo-accumulation index (Igeo), Contaminant Factor (CF), Pollution Load Index (PLI) and Sediment Quality Guideline (SQGs), low concentrations of metal were detected in sediment collected from seagrass bed and categorized as unpolluted. However, some of benthic organisms have been affected with metal concentrations in the coastal environment. Eggs of Tachypleus gigas consisted of As concentration over the threshold, while Family Pinnidae and Placuna sp. have high concentration of Cd and As. Stable isotope and metal analysis are perfectly combination to evaluate the biomagnification and biodilution of trace metal. Different in accumulations of metals in organisms depend on assimilation efficiencies and efflux rates of metals in organism. Movement of metals in seagrass ecosystem involved biota that correlated with stable isotope ratio of δ13C and δ15N. All selected trace metals have biodiluted throughout the seagrass food web. The concept of mobility of trace metals in seagrass ecosystem was clearly designed across the trophic level.